2009
DOI: 10.2478/v10085-009-0009-4
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and sorption of potentially toxic metals in four forest soils from Hungary

Abstract: Metals of natural and anthropogenic origin behave differently in soils mostly due to their different mobility. In this study, sequential extractions and batch sorption experiments were performed to relate the fractionation of native Ni, Cu, Zn and Pb to the sorption properties of added metals in four soils with contrasting physiochemical characteristics. A significant effect due to sample composition on both the mobility and sorption characteristics of these metals was found. The efficiency of soil components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…However, previously the lead originating from leaded gasoline could have accumulated in the roadside soils over several decades. Furthermore, lead has relatively limited mobility, and therefore it can remain and become concentrated in the soils [10,[54][55][56]. These results are in good accordance with the findings of other authors, who demonstrated that lead concentrations are significantly higher in roadside soils [6,57].…”
Section: Discussionsupporting
confidence: 88%
“…However, previously the lead originating from leaded gasoline could have accumulated in the roadside soils over several decades. Furthermore, lead has relatively limited mobility, and therefore it can remain and become concentrated in the soils [10,[54][55][56]. These results are in good accordance with the findings of other authors, who demonstrated that lead concentrations are significantly higher in roadside soils [6,57].…”
Section: Discussionsupporting
confidence: 88%
“…The clay mineral character of Boda Claystone is fundamentally illitic. Although swelling clay minerals, such as smectites and vermiculites have the largest cation exchange and adsorption capacity among clay minerals [22], illite has special sorption property for large cations with low hydration energy, such as caesium [23]. Illite and other mica-like minerals are excellent caesium adsorbents from low concentration solutions due to the presence of weathered, hydrated crystallite edges [24], the so called frayed edges.…”
Section: Aspects Concerning Radionuclide Sorption Propertiesmentioning
confidence: 99%
“…In this study, single element and competitive batch sorption experiments with Cu, Zn and Pb were performed on three different genetic horizons (A, B t and C k ) of a Luvisol profile. In an earlier work, Sipos [17] studied the relationship between the fractionation of native metals and sorption of added metals partly on the same samples. In this case, the aim of this study was to relate sorption parameters of the studied metals to the composition of the different horizons within the profile.…”
Section: Introductionmentioning
confidence: 99%